Attention profile: information to which we pay attention? - Orduña-Malea, Enrique (Anuario ThinkEPI, 2009)
Technology, a tool for better completing our daily tasks, could, if not mastered properly, be converted into a work barrier. That could produce a narrow vision that prevents focus on the true purpose of work. This can be seen in that little attention is given to metadata schemes without structured bibliographic descriptions. This paper outlines the schemes based on Attention profile, providing a brief introduction to the concept and outlining the two main standards that are trying to structure it, Apml and the recent Open Taste initiative.